The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1993
DOI: 10.1111/j.1365-2222.1993.tb00365.x
|View full text |Cite
|
Sign up to set email alerts
|

Formation of phosphatidylinositol‐4‐phosphate in human peripheral blood eosinophils

Abstract: To evaluate the presence of phosphatidylinositol-4-phosphate in peripheral blood eosinophils, venous blood was drawn from normal healthy volunteers. The eosinophils were isolated on a Percoll gradient and were incubated with [gamma32P]ATP in the presence of Mg2+. After stopping the reaction, lipid extraction was performed with acidic medium and phospholipids were separated by thin-layer chromatography on 1% (w/v) oxalic acid- and potassium oxalate-impregnated silica gel plates. Considerable amounts of radioact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

1993
1993
2009
2009

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Each tube con tained 7 x KP purified eosinophils. Incubations were carried out at 37°C for 15 min in a total volume of 100 pi, because these conditions were shown to be optimal for the reaction based on recent studies under various conditions for time, tem perature, and so on [4]. The reaction was stopped by the addition of methanol and chloroform in the acidic condition to the entire eosinophil suspension as described below.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Each tube con tained 7 x KP purified eosinophils. Incubations were carried out at 37°C for 15 min in a total volume of 100 pi, because these conditions were shown to be optimal for the reaction based on recent studies under various conditions for time, tem perature, and so on [4]. The reaction was stopped by the addition of methanol and chloroform in the acidic condition to the entire eosinophil suspension as described below.…”
Section: Methodsmentioning
confidence: 99%
“…A series of studies using guinea-pig peritoneal eosinophils [2,3] indicated the presence of stimulus-re sponse coupling in eosinophils, such as accumulation of inositol trisphosphate and subsequent mobilization of Ca2+, suggesting the presence of PtdIns(4,5)P2 in eosi nophils. However, to our knowledge, no information is available about the presence of PtdIns(4,5)P2 in human eosinophils, and very recently we reported that human peripheral blood eosinophils can produce phosphatidylinositol-4-phosphate [PtdIns(4)P] [4], Most PtdIns(4)P in cells is thought to be produced en zymatically from phospatidylinositol (Ptdlns) by Ptdlns kinase and the reaction requires ATP and Mg2+ [5]: Ptdlns + ATP-^ PtdIns(4)P + ADP. Ptdlns kinase appears to be widely distributed among mammalian tissues [6][7][8] and PtdIns (4,5)P2 is synthesized by stepwise phosphorylation of Ptdlns by Ptdlns kinase and PtdIns(4)P kinase.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The difficulty in isolating normal human eosinophils from peripheral blood in sufficient number, yet without contamination by other cell types, for the investigation of signal transduction mechanisms has hampered progress in this area of research. Consequently, while there are a few studies using normal human eosinophils, for example see the article by Kurosawa et al in this issue [1], others have used cells isolated from patients with hypereosinophilic syndrome (HES) [2]. The altered density, metabolism and surface receptors of these cells indicate that activated eosinophils circulate in HES [3].…”
mentioning
confidence: 99%
“…PAF receptors are coupled to the pertussis toxin-sensitive Gi protein which, it is suggested, transduces ligand binding to effector systems, possibly phospholipase C [37]. The presence of phosphatidylinositol kinase in normal human eosinophils [1] indicates the machinery is in place for receptormediated phosphoinositide turnover and subsequent generation ofthe short-lived intracellular second messengers, diacylglycerol and inositol trisphosphate. Diacylglycerol produced in the plasma membrane, either as a direct result of phospholipase C activation or indirectly via the action of phospholipase D on cholinephospholipids [38], induces tbe translocation and activation of PK-C, whilst inositol trisphosphate raises intracellular Ca^+ levels by inducing Ca^+ release from endoplasmic reticulum.…”
mentioning
confidence: 99%